Gender, Technology, and Libraries - Lamont, Melissa (Information Technology and Libraries, 2009)
Information technology (IT) is vitally important to many organizations, including libraries. Yet a review of employment statistics and a citation analysis show that men make up the majority of the IT workforce, in libraries and in the broader workforce. Research from sociology, psychology, and women’s studies highlights the organizational and social issues that inhibit women. Understanding why women are less evident in library IT positions will help inform measures to remedy the gender disparity.